Changing profiles of cancer burden worldwide and in China: a secondary analysis of the global cancer statistics 2020 - Cao, Wei; Chen, Hong-Da; Yu, Yi-Wen; Li, Ni; Chen, Wan-Qing (Chinese medical journal, 2021)
Cancer is one of the leading causes of death globally, but its burden is not uniform. GLOBOCAN 2020 has newly updated the estimates of cancer burden. This study summarizes the most recent changing profiles of cancer burden worldwide and in China and compares the cancer data of China with those of other regions. We conducted a descriptive secondary analysis of the GLOBOCAN 2020 data. To depict the changing global profile of the leading cancer types in 2020 compared with 2018, we extracted the numbers of cases and deaths in 2018 from GLOBOCAN 2018. We also obtained cancer incidence and mortality from the 2015 National Cancer Registry Report in China when sorting the leading cancer types by new cases and deaths. For the leading cancer types according to sex in China, we summarized the estimated numbers of incidence and mortality, and calculated China's percentage of the global new cases and deaths. Breast cancer displaced lung cancer to become the most leading diagnosed cancer worldwide in 2020. Lung, liver, stomach, breast, and colon cancers were the top five leading causes of cancer-related death, among which liver cancer changed from the third-highest cancer mortality in 2018 to the second-highest in 2020. China accounted for 24% of newly diagnosed cases and 30% of the cancer-related deaths worldwide in 2020. Among the 185 countries included in the database, China's age-standardized incidence rate (204.8 per 100,000) ranked 65th and the age-standardized mortality rate (129.4 per 100,000) ranked 13th. The two rates were above the global average. Lung cancer remained the most common cancer type and the leading cause of cancer death in China. However, breast cancer became the most frequent cancer type among women if the incidence was stratified by sex. Incidences of colorectal cancer and breast cancer increased rapidly. The leading causes of cancer death varied minimally in ranking from 2015 to 2020 in China. Gastrointestinal cancers, including stomach, colorectal, liver, and esophageal cancers, contributed to a massive burden of cancer for both sexes. The burden of breast cancer is increasing globally. China is undergoing cancer transition with an increasing burden of lung cancer, gastrointestinal cancer, and breast cancers. The mortality rate of cancer in China is high. Comprehensive strategies are urgently needed to target China's changing profiles of the cancer burden.